"It's not how I use it, but what I believe about it": The role of experience in the online information seeking behavior - Stolero, Nathan; Segev, Elad (AoIR Selected Papers of Internet Research, 2017)
The study employs a qualitative approach, using 44 semi-structured interviews with internet users, in order to compare the perceptions of adolescents, young adults and adults towards the information seeking process and their information seeking behavior. When it comes to experience with information technology, most scholars refer to actual uses, the confidence in technology use, and skills or digital literacy. Recent studies questioned this definition, arguing that the experience with information technologies is not only about the actual uses, but also how users experience it. In addition, very little consideration has been given to the fact that the different experience that different age groups have with information technologies can explain much of the information seeking behavior differences. Five themes emerged from the interviews: different perceptions of information, the role of negative emotions in the information seeking process, beliefs towards passive and incidental information seeking behavior, selection of information and information evaluation. The theoretical contribution of this study is in re-conceptualizing the role of experience with information technologies as part of the existing models of information seeking behavior. Based on their shorter experience with information seeking processes adolescents presented a less matured understanding of information, and reported on less structured seeking behavior than adults. This practice was led by intense emotions, often depended on the algorithm, and required more sophisticated ad-hoc evaluation criteria. Adults reported on a more structured and conservative strategies, which they believed protected them from wasting time, and kept them in much more control over the process.